2015
DOI: 10.1007/s00500-015-1648-y
|View full text |Cite
|
Sign up to set email alerts
|

Objective reduction based on nonlinear correlation information entropy

Abstract: It is hard to obtain the entire solution set of a many-objective optimization problem (MaOP) by multiobjective evolutionary algorithms (MOEAs) because of the difficulties brought by the large number of objectives. However, the redundancy of objectives exists in some problems with correlated objectives (linearly or nonlinearly). Objective reduction can be used to decrease the difficulties of some MaOPs. In this paper, we propose a novel objective reduction approach based on nonlinear correlation information ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 56 publications
0
35
0
Order By: Relevance
“…Existing research on MaOPs can be roughly divided into four categories, objective reduction [32], [33], incorporation of preferences [34], modified dominance relationships, and introduction of additional selection criteria. In case there is a strong correlation between objectives, some objectives can be removed [35].…”
mentioning
confidence: 99%
“…Existing research on MaOPs can be roughly divided into four categories, objective reduction [32], [33], incorporation of preferences [34], modified dominance relationships, and introduction of additional selection criteria. In case there is a strong correlation between objectives, some objectives can be removed [35].…”
mentioning
confidence: 99%
“…Reference [20] transformed MaOPs into several single-objective optimization problems by aggregation functions with a series of weight vectors, but its performance on MaOPs with highly correlated objectives is modest. An objective reduction approach was proposed in [21] to select the most conflicting objectives during the execution of MOEAs, and simulation results showed that this approach improved the performance of Pareto-based MOEAs significantly. However, this objective reduction approach might be ineffective for MaOPs without redundant objectives.…”
Section: Introductionmentioning
confidence: 99%
“…The conflict might be global or local [141][142][143]. For locally conflicting objectives, they are conflicting with each other in some regions but not in other regions.…”
Section: Relationship Between Objectivesmentioning
confidence: 99%